Evaluation of dental status in relation to excessive horizontal and vertical overlap in North Indian population - Anil Raj (Journal of Pharmacy and Bioallied Sciences, 2021)
Introduction: Tooth wear (attrition) is a multifactorial entity, the pathogenesis of which involves many factors but the role of malocclusion cannot be undermined. Overjet and overbite play an important role in defining occlusion, hence they should also play an important role in causing attrition. Objectives: This study aims to evaluate the relationship of dental health status between the vertical and horizontal overlap. Materials and Methods: This study was conducted on 600 patients selected randomly from rural population which were divided into three equal groups as per the predefined criteria, namely, horizontal overlap, vertical overlap, and control group. All patients were examined for the tooth attrition. Results: In Group 1 – 73 patients out of 200 showed one or more teeth attrition, in Group 2 – 38 patients out of 200 showed one or more teeth attrition, and in the control group, 22 patients out of 200 showed one or more teeth attrition. Conclusion: It was concluded that both vertical and horizontal abnormal relationships of teeth play an important role in the etiology of attrition, with abnormal horizontal overlap being the more detrimental as compared to the vertical one.